CLINICAL AND ETILOGICAL PROFILE OF NEW ONSET FOCAL SEIZURES - Dr. N.N.ANAND,; Dr. KRISHNA CHAITANYA ALAM,; Dr.V.PADMA, (International Journal of Pharma and Bio Sciences, 2015)
To evaluate the etiological profile of new onset focal seizures in adults with the help of neuroimaging studies, Immunological methods in a tertiary care hospital in Chennai. 50 Cases of new onset focal seizures were included in the study. The etiology was determined by neuroimaging and appropriate investigations were done. In the age group of 18-70 yrs maximum cases were seen between 18-30 yrs (48%).18 (36.0%) were simple focal, 28 (56%) were complex focal, 4 (8%) were secondary generalized. CT scan showing localization to the parietal lobe in 36.1% cases. The associated symptom of headache is seen in13.8% cases. Vomiting in 16.6% cases Fever in 25% of cases. Loss of consciousness in 8.3% of cases. Automatisms seen in 4% of cases. In our study Complex focal Seizures are the most common focal Seizure Type. The age group, most commonly affected is 18 to 30 years. Granulomatouslesions & Cerebro vascular accidents are the most common cause of Focal Seizure in younger age groups. Among Central Nervous System infections/granulomatous lesions of brain, Neurocysticercosis & tuberculomas are most common. Incidence in male is more than in female.